NEGATIVE IMPACT AND IMPACT OF POPULAR CULTURE ON YOUTH EDUCATION - Yunusaliyva Nargiza Ortiqjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the negative consequences and influence of mass culture on the education of young people, and also comments on the negative effects that arise in society.